Mine Design of Laterite Nickel Ore Based on Pit Limit Optimization with Floating Cone Method at Meranti Pit of PT Ang and Fang Brother (JURNAL GEOCELEBES, 2023)
PT Ang and Fang Brother Site Lalampu is a nickel laterite mines company located at Lalampu Village, Morowali Regency, Central Sulawesi Province. The purpose of research is to determine the ultimate pit limit using floating cone method and calculate the net present value (NPV), to design the ultimate pit limit at Front 8 of Meranti Pit (one of the company’s fronts), to calculate the mined laterite nickel reserves and the overburden based on the pit design. The data used are block model data, topography, capital and operating costs, commodity price, density, geotechnical data, mine recovery 85%, cut-off grade 1.3%, and the company's production target of 50,000 tons/month. Data processing generates Pit Shell 9 as the ultimate pit limit with ore recovery of 264,375 tons from 284,063 tons of Front 8 resources. Based on the design using Micromine 2021 software with an area of 5.25 hectares, a total of 234,142 tons laterite nickel ore obtained by stripping 389,063 BCM of the overburden, and it still economical with stripping ratio value (1.66 BCM/ton), smaller than the BESR value (6.32 BCM/ton). The amount of nickel laterite reserves produced based on mine recovery of 85% is 199,021 tons so the life of mine lasted 3.98 months.
Keywords: Laterite nickel; pit optimization; pit design